Transverse-momentum-dependent Multiplicities of Charged Hadrons in Muon-Deuteron Deep Inelastic Scattering - Aghasyan M. Mher; Burtsev V. E. Vitaly Evgenjevich; Dusaev R. R. Renat Ramilyevich; Levchenko E. A. Evgeny Anatolievich; Mamon S. A. Sergey Aleksandrovich; Chumakov A. G. Aleksandr Grigorjevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Vasilishin B. I. Bogdan Ivanovich (2018, 2018)
Title screen